WORKING AND STUDYING: CHALLENGES FACED BY THE DIPLOMA NURSE WHILE UPGRADING - Kamau, S; Mwangi, J (Global Journal of Health Sciences, 2021)
Background: Personal development and pursuance of higher education in nursing is considered important for the nurses to stay abreast in the dynamic medical world and promote excellence in practice. There are workplace barriers that cause challenges for nurses who are upgrading as well as after upgrading. Objectives: Determine institution related challenges that determine whether a nurse enrolls in a diploma to degree nursing program, their performance during the program and their decision to hold on to the end Methodology: The study adopted a descriptive cross sectional design, carried out among a randomly sampled population of 220 nurses who work in the hospital. Data was collected using self-administered questionnaires from a simple random sample of 140 nurses. Data analysis was done by SPSS version 22.0. Measures of central tendency mean and range were used. The findings have been presented in form of figures, tables, pie-charts and narrative texts. Results: A total of 120 participants filled questionnaires representing an 85% response rate. 78% (n=93) were female, and 22% (n=27) were male, Inferential analysis on institution related factors and their influence on upgrading nurses were assessed. Findings showed that the need for a promotion was the most important institution -related factors (n=62, 57.4%) underlying the motivation for nurses to upgrade (X2=17.601, df=7, p=0.014). Conclusion: Upgrading is a worthwhile venture for both the nurse and the work place. Promotion is one of the greatest motivational factors of upgrading. More diploma nurses think it is worth to upgrade. Recommendations: This research recommends that a caring curriculum should be designed for the working nurse and recognition and promotion according to education level and awareness of policies on promotion after upgrading.